STRUKTURALISME DALAM GANDRUNG BANYUWANGI: PAKAIAN DAN GERAKAN (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2024)
The presence of Gandrung as a typical art of Banyuwangi is known to have helped build structures that show the behavior and mindset of the Using people. This can be seen in every arrangement of movements and clothing this art uses. For this reason, this research was prepared to analyze the structuralism of Gandrung Banyuwangi through clothing and movement. The research method used is qualitative through interview techniques and reading literature from previous research. The analysis process was carried out using Saussure's structuralism approach. The results of the study show that as a typical art, Gandrung Banyuwangi is unique in the arrangement of clothing and movements presented, where each knick-knack and act presented symbolizes uniqueness for the community that formed it, which refers to Gandrung not only existing as an entertaining art but also